A new species of Thinophilus Wahlberg (Diptera: Dolichopodidae: Hydrophorinae) from coastal India with re-description of Thinophilus tesselatus Becker (Diptera: Dolichopodidae: Hydrophorinae) - Mukherjee, Koustav; Pramanik, Debdeep; Naskar, Atanu; Banerjee, Dhriti (Zootaxa, 2023)
A new peculiar species of marine dolichopodid fly from West Bengal, India is described: Thinophilus maritimus Mukherjee & Pramanik sp. nov. COI barcodes of the new species were compared to other available Thinophilus sequences. Despite the lack of lateral setae on its hind coxa, this species clusters within the Thinophilus group. Males of Thinophilus tesselatus Becker, 1922 were also obtained from the same area, and a detailed redescription of the species is presented here. A checklist of 70 Oriental Thinophilus species is also provided.